Implementasi P5 berbasis kewirausahaan dalam meningkatkan entrepreneurial skills peserta didik kelas xi di MA Darussalam Kampung Baru Oki - Nur Tia Ningsih; Miftakhur Rohmah; Siti Afifah (Universitas Negeri Surabaya, 2026)
This study aims to analyse the implementation of the Pancasila Student Profile Strengthening Project (P5) based on entrepreneurship through eco-printing techniques at MA Darussalam Kampung Baru OKI. Using a qualitative approach with grounded theory, this study involved 33 students from class XI.1 who were selected through cluster sampling. Data were obtained through interviews, observations, and documentation, then analysed through data reduction, data presentation, and conclusion drawing. The results showed that the eco-print-based P5 was effective in improving students' entrepreneurial skills, particularly in creativity, cooperation, time management, and initiative. School support, utilisation of environmental potential, and active student participation were key factors that drove the success of the implementation, while also increasing students' motivation, confidence, and self-efficacy to engage in entrepreneurship outside of school. Thus, eco-print-based P5 serves as a medium for contextual learning as well as a strategy for shaping an independent, innovative, and competitive generation.